Peer review in writing activities: outcomes and perceptions of EFL students - Theresia Adventris Ndohna Ruru; Teguh Sulistyo (Journal of Research on English and Language Learning (J-REaLL), 2020)
This study aims at investigating the effect of peer review on students' writing ability and the students' perceptions toward the use of peer review technique in writing class. This is an experimental research by involving 62 EFL students of eighth graders of a Junior High School in Malang, Indonesia. The data were obtained by conducting a writing (pre-test an post-test) and giving questionnaire. The data were analyzed by using quantitative descriptive statistics. The qualitative data expressed descriptively about students perceptions toward using peer review technique in writing acitvity. The findings shows that the students in experimental group who were taught by using peer review technique got better achievement in writing ability than the students in control group who were taught by using self-assessment strategy. The use of peer review technique in writing class makes the class less anxious and more enjoyable. The students are enthusiastic so that the class become more student-centered. The students are able to interact each other in giving comments and suggestions to reduce mistakes in terms of global and local issues to make better subsequent of writing product. In addition, the result of questionnaire shows that the students have positive attitudes toward the use peer review technique in writing class.